Pengaruh Pengangguran terhadap Kemiskinan di Provinsi Sumatera Utara - Meiriza, Mica Siar; Sidebang, Tamaria Br.; Ginting, Renata Olivia; Kaban, Novita Sari Br.; Situmorang, Eva Juli Yanti; Firmansyah, Deyren; Annurradi, M Abdan Syakura (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Unemployment and poverty are two social problems that are often interrelated in the context of a region's economic development. North Sumatra Province, as a province that has a variety of potential resources, also faces serious challenges related to unemployment and poverty. This research aims to analyze the influence of unemployment on poverty in North Sumatra Province. In carrying out this research, the researcher used a research method, namely the quantitative method of inferential statistics. The data used in this research is secondary data where this data was obtained by the author from the publications of the Central Bureau of Statistics (BPS) of North Sumatra Province from 2013-2022. And the data used is data on unemployment and poverty rates in North Sumatra Province. This research tests the influence of the independent variable on the dependent variable and the technique used uses SPSS which is analyzed using the classic assumption test, heteroscedasticity test, multicollinearity test, and simple regression test. The regression coefficient shows that the higher unemployment is, the more poverty tends to increase. And as for the research results obtained, namely the calculated t value is greater than the t table, then H0 is rejected. This means that there is a positive and significant influence of unemployment on poverty in North Sumatra.